Guidelines for Using Instructional Materials of Vocational Education in Thailand during COVID-19 - Hinon , Kanitta; Seubpradit , Lanlalit (International Journal of Educational Communications and Technology, 2022)
The This information on the guidelines for manipulating of online learning materials of Thai vocational education during school closures due to COVID-19 has been based on document-analysis research techniques. The results showed that during the closure of academic institutions, the learning system continued. It allows vocational schools to maintain a policy of managing learning in the similar direction. Teaching and learning at the Vocational Education Institutes of Thailand use On-Site, On-Air, Online and On-demand learning methods. The Ministry of Education has included on-hand learning methods together with online learning management with various methods including Synchronous, Asynchronous, Hybrid Learning & Blended Learning. While on-site teaching uses Project-based Learning, STEM and STEAM management. As for On-Air teaching and learning, R-radio and TV Thai-com are primarily used. On-demand, it’s an informal study via YouTube, R-Channel. On-hand will deliver books for learners to learn by themselves at home. These policies and actions make it possible for vocational education institutions to continuously provide teaching in the Covid-19 situation.